Turn coat - Butcher, Jim, 1971- (New York : Roc, 2009)
Harry must uncover a traitor within the Wizards of the White Council, keep a less-than-agreeable warden under wraps, and avoid coming under scrutiny himself. And a single mistake may cost someone his head--someone like Harry.
Keywords: Dresden, Harry (Fictitious character) -- Fiction; Wizards -- Fiction; Chicago (Ill.) -- Fiction; Fantasy fiction